Assessment of the impact of venture capital investment on labour productivity: an analysis of the EU countries - Padgureckienė, Aistė; Cibulskienė, Diana (Journal of Business Economics and Management, 2024)
This study investigates the impact of venture capital investments on the labour productivity of the European Union countries. Considering the fact that there is a lack of research on evaluating the effects of venture capital investments on labor productivity at the country level, the methodology designed in this article is used to assess heterogeneous impact of venture capital investments, which is determined by the innovative environment or financial development factors, on labour productivity in 25 EU countries. Panel data of 25 European Union countries were used for the regression analysis. The findings of the empirical study show that the volume of venture capital investments does not determine the growth of labour productivity in the analysed countries. Such results can be explained by the economic findings presented by other researchers. Some of the studies found that it is not venture capital investments that determine economic growth, innovation or technological development, but these economic phenomena increase venture capital investment. Based on statistical data, the greatest need for venture capital investments in Europe is in sectors that develop new technologies and in the information and communication technology sector. Therefore, the volume of venture capital investments in the analysed countries is too small at the macroeconomic level and their effect on labour productivity is manifested at the level of companies or specific sectors.